The Bio‐SANS instrument at the High Flux Isotope Reactor of Oak Ridge National Laboratory. (1st August 2014) - Heller, William T.; Urban, Volker S.; Lynn, Gary W.; Weiss, Kevin L.; O'Neill, Hugh M.; Pingali, Sai Venkatesh; Qian, Shuo; Littrell, Kenneth C.; Melnichenko, Yuri B.; Buchanan, Michelle V.; Selby, Douglas L.; Wignall, George D.; et al.
<x xml:space="preserve">Abstract</x> Small‐angle neutron scattering (SANS) is a powerful tool for characterizing complex disordered materials, including biological materials. The Bio‐SANS instrument of the High Flux Isotope Reactor of Oak Ridge National Laboratory (ORNL) is a high‐flux low‐background SANS instrument that is, uniquely among SANS instruments, dedicated to serving the needs of the structural biology and biomaterials communities as an open‐access user facility. Here, the technical specifications and performance of the Bio‐SANS are presented. Sample environments developed to address the needs of the user program of the instrument are also presented. Further, the isotopic labeling and sample preparation capabilities available in the Bio‐Deuteration Laboratory for users of the Bio‐SANS and other neutron scattering instruments at ORNL are described. Finally, a brief survey of research performed using the Bio‐SANS is presented, which demonstrates the breadth of the research that the instrument's user community engages in.